Tuberculosis its Prevalence, Complications and Clinical Aspects among the Population of Northern Part of Bihar - Kumar, Chandan; Kumar, Dr. Naresh (South Eastern European Journal of Public Health, 2024)
Introduction: It is commonly known as death causing disease of reproductive age group people. It is one of the top five death causing disease. It effects upon every age group people. But dangerous impact of tuberculosis occurs on immunocompetent people. There are a number of complications occur only due to one disease that is tuberculosis. it effects almost all organs and impaired their vital functions. Even if we leave death, even after tuberculosis proved to be most dangerous disease. In this study our main aim to explore the aspects, complications and prevalence of genital tuberculosis. In this study we also explore the ancient technics as well as the modern technics and their methods to ruled out the disease and improvement of treatment from ancient time to modern time. Method: This study was carried out between January 22 to April 23. 342 subjects are selected by inclusion and exclusion method. Subjects are classified in to 3 groups according to their physical appearance clinical symptoms and family history. Further patients are again classified in to negative, positive and doubtful negative patients after conducting routine and special investigations. Results: After all pathological investigation we found that 45 (13.1%) subjects have found positive in which 5.8% were male and 7.2 % were female. Conclusion: Tuberculosis is present in different forms and should be ruled out in early stage to safe from tissue damages. But unfortunately, we haven’t any tools which can detect the disease in its early stage accurately. All the investigation has their own limitations and contamination errors. There are a number of patients in which some can easily identified by their clinical symptoms and related routine examination, some are asymptomatic and identified by advanced diagnostic tools where are some such patient are also found who were strong symptomatic but even not only routine but also advance investigations are fail to detect. In our study we found the root cause of the disease, which are high population density, economically lower standard, poor hygiene life style, compromise food habits, illiteracy, marriage in early stage, multiple marriage, multiple children, non- skilled medical practices are causing and enhancing the incident of tuberculosis.